2021
DOI: 10.3389/fimmu.2021.786680
|View full text |Cite
|
Sign up to set email alerts
|

Inducible T-Cell Costimulator Mediates Lymphocyte/Macrophage Interactions During Liver Repair

Abstract: The liver capacity to recover from acute liver injury is a critical factor in the development of acute liver failure (ALF) caused by viral infections, ischemia/reperfusion or drug toxicity. Liver healing requires the switching of pro-inflammatory monocyte-derived macrophages(MoMFs) to a reparative phenotype. However, the mechanisms involved are still incompletely characterized. In this study we investigated the contribution of T-lymphocyte/macrophage interaction through the co-stimulatory molecule Inducible T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…These results are in keeping also with recent findings showing that ICOS-Fc protects against liver damage through a shift of pro-inflammatory monocyte-derived macrophages to an anti-inflammatory phenotype (20). In parallel, the direct renoprotective effect triggered by ICOS-Fc treatment is supported by a recent study showing a key role of ICOSL in preventing early kidney disease, possibly through a selective binding to podocyte avb3 integrin, in which ICOSL serves as an avb3-selective antagonist that maintains adequate glomerular filtration (36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in keeping also with recent findings showing that ICOS-Fc protects against liver damage through a shift of pro-inflammatory monocyte-derived macrophages to an anti-inflammatory phenotype (20). In parallel, the direct renoprotective effect triggered by ICOS-Fc treatment is supported by a recent study showing a key role of ICOSL in preventing early kidney disease, possibly through a selective binding to podocyte avb3 integrin, in which ICOSL serves as an avb3-selective antagonist that maintains adequate glomerular filtration (36).…”
Section: Discussionsupporting
confidence: 92%
“…These ICOS-Fc effects can also be recorded in dendritic cells (DC), along with modulated cytokine release and antigen cross-presentation in class I major histocompatibility complex molecules (13), while in osteoclasts, ICOS-Fc inhibits differentiation and function (18). In vivo, ICOS-Fc inhibits tumor growth and metastasis, development of osteoporosis, liver damage induced by acute inflammation following treatment with CCl4, and it favors skin wound healing (18)(19)(20)(21). Nevertheless, little is known about the molecular mechanism(s) involved in ICOSL-mediated inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the effects of ICOS-Fc on wound healing are in line with our previous work showing that CCl 4 -treated ICOS −/− or ICOSL −/− mice develop a more severely acute inflammatory liver damage, along with a reduction of reparative macrophages, compared to their wild-type counterparts. Moreover, treatment with ICOS-Fc protected ICOS-deficient mice from this increased damage, simultaneously restoring the number of reparative macrophages, whereas it had no effects in ICOSL −/− mice [17]. These findings are also in line with the aforementioned study by Maeda et al [15], showing that mice lacking ICOS and/or ICOSL display decreased angiogenesis and a reduction of T cells and macrophages at the wound site.…”
Section: Discussionsupporting
confidence: 88%
“…In good agreement with a role of the ICOS/ICOSL dyad in normal tissue repair, we have recently shown that CCl 4 -induced liver damage, which is dependent on massive recruitment of blood-derived monocytes/macrophages, is dramatically worsened in both ICOS −/− and ICOSL −/− mice [17]. Interestingly, we were able to rescue this impairment by treating mice with ICOS-Fc, a recombinant soluble protein composed of the ICOS extracellular portion fused to the IgG1 Fc portion, which has been previously shown to trigger ICOSL, thereby inhibiting the development of experimental tumor metastases in vitro and tumor angiogenesis in vivo [9,11,17,18].…”
Section: Introductionmentioning
confidence: 83%
“…However, whether CDC20 works in acute liver failure remains unclear. This study innovatively adopted the CDC20 inhibitor Apcin for treating ALF, and a significant therapeutic effect was achieved in the mouse model of ALF (Ramavath et al, 2021). PTTG1, CENPF, KIF4, KIF11, NUSAP1, and TPX2 have also been implicated in many biological functions, such as DNA repair, organ development, and regulation of mitosis (Försti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%